Some Aspects of Voltage Source Inverter Control - Rymarski, Zbigniew; Bernacki, Krzysztof; Dyga, Lukasz (Elektronika ir Elektrotechnika, 2017)
The model of a voltage source inverter depends on its output filter. The parameters of this filter can differ significantly from their nominal values due to power losses in the core of the output coil and changes in its inductance. Only Multi-Input-Single-Output control systems can effectively reduce inverter output voltage distortions for a standard nonlinear rectifier RC load. However, their design requires knowledge of the actual values of the inverter parameters. The novelty of the paper is that it connects the designs of two MISO control systems with a method of the automated measurements of the voltage source inverter parameters. The breadboard verification is also included. DOI: http://dx.doi.org/10.5755/j01.eie.23.2.17995